Through a Venice Glass Darkly: John Foxe’s Most Famous Miracle - Freeman, Thomas S. (Studies in church history, 2005)
On New Year’s Day, 1578, Sir John Langley, a wealthy alderman of the City of London, lay dying. Present at his deathbed were three of the most eminent preachers in the capital: Robert Crowley, who held four London livings, Alexander Nowell, the dean of St Paul’s cathedral and John Foxe, the martyrologist. As Langley’s life ebbed away, Foxe went up to the dying man and ‘used both godly councell unto him and some devote prayers’. Since Langley could no longer speak, Foxe urged him to signify his belief in Christ by holding up his hands: Ymmediatly so he did and then … Mr Fox was verie gladd, and told him that he had done ynoughe to show him self both a Crystian and to depend only uppon the merittes of Chrystes passione.